Principal leadership and educational excellence - Ng, Chee Heng (1998)
This study, which was qualitative in nature, seek to find a better understanding on how and why the seven experienced secondary school principals being interviewed, who were considered to be high performers, had run their schools successfully and efficiently. Data collected was organized into different themes and categories, which was then compared to various school leadership and management theories observed in the literature. The main literature and research finding which prompted this survey were: i) the concept of school leadership as suggested by Pounder et. al. (1995), where the researchers contented that school leaders might include the Principal, senior teachers, parents or even students; ii) the concept of 'policy leadership' as suggested by Azahari (1994); and iii) the Burke-Litwin's Model of change and performance (1992). In this study, seven experienced secondary school principals (having a 00-2 grade in average) in and around the Klang valley were interviewed and asked on a series of questions regarding current educational issues and topics. Additional information was obtained through observations and documents in the schools. This study was intended to categorize opinions and experiences of the principals so as to have a better understanding on the concept of 'effectiveness' in their schools and its relation to certain traits of the principals. Hence data collected was used to facilitate the discovery of knowledge about how leadership behaviour of administrators was organized. This was then discussed under six main categories, namely: 1) the principals' perceptions of their leadership roles and responsibilities; 2) the principals' perceptions on educational policies; 3) the principals' perceptions on role accountability; 4) the principals' perceptions on management theories; 5) the principals' administrative approaches; and 6) the principals' approaches to improve school effectiveness. Some of the opinions of the principals interviewed were summarized as follow: 1) School effectiveness depended on the academic achievement of the schools, and it depended on the 'input' or the qualities of the students; 2) The 'popularity' of a school does not equate to its effectiveness; 3) The objectives of the schools were more 'shaped' and 'influenced' by the aspirations of the parents, rather than the national objectives of the country; 4) School principals do not participate in deciding on policy' matters, as these are decided at the top. The school principals are 'policy leaders'; 5) Performing principals had the capability of exercising the 'limited power' as policy leaders to instruct their subordinates to perform. This they do it through the exercise of' informal powers' like being informative, leadership by example, having a 'good network' with the people in high positions etc.; 6) The New Remuneration System (SSB) is good in theory, but it is tedious and time-consuming to have it fully carried out in the schools; 7) The SMART-school concept was received generally with skepticism. The concept was perceived as one that links to high-tech aids like computers, Internet communications etc. 8) Soliciting external funds was of the utmost priority and responsibility of the ambitious school principals; 9) School principals and school leadership should have a shift in the paradigm to adjust to the changing times of the Information Technology era and 10) School principals should be leaders and managers in their own right.